Labelling and quality of antimicrobial products used in chicken flocks in the Mekong Delta of Vietnam. Issue 4 (2nd August 2019) - Yen, Nguyen Thi Phuong; Phu, Doan Hoang; Van Cuong, Nguyen; Kiet, Bach Tuan; Hien, Be Vo; Padungtod, Pawin; Truong, Dinh Bao; Thwaites, Guy E.; Carrique‐Mas, Juan J.
Abstract: Background: The Mekong Delta of Vietnam is a hotspot of antimicrobial use (AMU), but there is no information on the quality of the labelling and strength of antimicrobial products used in poultry production. Methods: Based on a large random sample of farms, we identified the 20 most used antimicrobial products in the area, and investigated their antimicrobial active ingredient (AAI) content by UPLC‐MS/MS (91 analytical tests). Results: Only 17/59 (28.8%) batches contained all AAIs within 10% of the declared strength. Worryingly, 65.0% products provided in their label preparation guidelines for both therapeutic and prophylactic use. Withdrawal times for both meat and eggs were stated in 8/20 (40%) products. Conclusion: Results highlight deficiencies in quality and labelling contents that undermine authorities' efforts to discourage inappropriate use of antimicrobials. Abstract : We analysed the quality (strength) and labelling of 20 most commonly used antimicrobial products from a large representative survey of chicken farms in the Mekong Delta of Vietnam. The study identified a large proportion of products (71.9%) containing quantities of active ingredient outside the permitted range, as well while 65% of these products explicitly advised on prophylactic use (i.e. to prevent disease).